2009
DOI: 10.1159/000256661
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Human Erythrocyte Actin following Exposure to Hypoxia

Abstract: In a comparative study on erythrocytes (RBCs) drawn from mountaineers before and after a high-altitude stay, we observed that upon returning to sea level, their RBCs displayed a senescent-like phenotype as indicated by their density and the partial loss of membrane proteins which are shed by ageing RBCs. The aim of this study was to investigate possible changes in the membrane skeleton of these RBCs and to compare them with pathological RBCs. We analysed the proteins of RBC ghosts obtained from our subjects be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The ATP content of RBCs isolated during the deacclimatization from hypoxia was significantly higher than that of the control populations. Furthermore, alteration in the membrane-skeleton was found by a proteomic analysis, i.e., fragmentation of spectrin and actin (Risso et al, 2010). Finally in an investigation on blood samples drawn from mountain climbers, over and immediately after a 17 days' time spent at 3100–5600 m a.s.l., we observed that high altitude induced the expression of foetal haemoglobin.…”
Section: Experiments On Rbcs Subsetsmentioning
confidence: 99%
“…The ATP content of RBCs isolated during the deacclimatization from hypoxia was significantly higher than that of the control populations. Furthermore, alteration in the membrane-skeleton was found by a proteomic analysis, i.e., fragmentation of spectrin and actin (Risso et al, 2010). Finally in an investigation on blood samples drawn from mountain climbers, over and immediately after a 17 days' time spent at 3100–5600 m a.s.l., we observed that high altitude induced the expression of foetal haemoglobin.…”
Section: Experiments On Rbcs Subsetsmentioning
confidence: 99%
“…Hypoxia-reoxygenation diminishes band 3 protein functions in human erythrocytes, leading to actin rupture and cytoskeletal destabilization in vivo. 38
Figure 2 Hypoxia affects the deformability of erythrocyte membrane (A) Competition of deoxyHb with ankyrin for band 3 reduces erythrocyte membrane deformability by separating the cytoskeleton from the membrane. (B) The way of NO production under different hypoxia levels and its multiple effects on erythrocyte membrane deformability.
…”
Section: Hypoxia Affects Erythrocyte Membrane Propertiesmentioning
confidence: 99%
“…The transition from discoid to spherocytes vividly depends on intracellular calcium increase. It also correlates with microvesicle decrease in extracellular liquid and varying sensitivity to hydrolytic phospholipase A 2 [50,51]. Phosphatidylcholine content change (a key component of the RBC membrane bilipid layer) affects the discoid-to-echinocyte and discoid-tostomatocyte transitions significantly.…”
mentioning
confidence: 99%